NORMS FOR THE PUBLIC REMEMBRANCE OF NONHUMAN ANIMALS - McLennan, Matthew (Ethics, Politics & Society, 2023)
This article builds upon Avishai Margalit’s distinction between ethical and moral norms of remembrance. While Margalit is limited by his broadly Kantian framework and restricts his arguments to the remembrance of human beings, the author will argue that the resources exist both in his account and in the particularities of Canadian public life to a) account philosophically for what minimal public ethical norms are in place for the remembrance of nonhuman animals, and b) point towards a more robust, properly moral account of nonhuman animal remembrance. The author will take a recent Canadian case study in the public remembrance of nonhuman animals– the 2012 Animals in War Dedication – to show how existing norms are inherently unstable, pointing beyond themselves to a more species-inclusive, properly moral public perspective.